2015
DOI: 10.1038/srep13944
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Bacterial Identification, Resistance, Virulence and Type Profiling using Selected Reaction Monitoring Mass Spectrometry

Abstract: Mass spectrometry (MS) in Selected Reaction Monitoring (SRM) mode is proposed for in-depth characterisation of microorganisms in a multiplexed analysis. Within 60–80 minutes, the SRM method performs microbial identification (I), antibiotic-resistance detection (R), virulence assessment (V) and it provides epidemiological typing information (T). This SRM application is illustrated by the analysis of the human pathogen Staphylococcus aureus, demonstrating its promise for rapid characterisation of bacteria from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 45 publications
0
57
0
Order By: Relevance
“…If needed, more targeted proteins could be easily monitored; the method was very far from the multiplexing capabilities of SRM. Moreover, the robustness of SRM hyphenated with standard chromatography was shown to be compatible with clinical applications (19,51). A targeted strategy seems therefore a good compromise to accurately measure a reasonable number of proteins and to address biological questions at the protein level.…”
Section: Quantitative Protein Measurement Using Targeted Msmentioning
confidence: 99%
See 3 more Smart Citations
“…If needed, more targeted proteins could be easily monitored; the method was very far from the multiplexing capabilities of SRM. Moreover, the robustness of SRM hyphenated with standard chromatography was shown to be compatible with clinical applications (19,51). A targeted strategy seems therefore a good compromise to accurately measure a reasonable number of proteins and to address biological questions at the protein level.…”
Section: Quantitative Protein Measurement Using Targeted Msmentioning
confidence: 99%
“…As in previous studies (18,19), the quality of the protein measurements was assessed by verifying the preservation of the ratio between transitions belonging to the same protein. The quantities of quantotypic peptides from a given protein should be equimolar if they are not impaired by posttranslational modifications, stochastic digestion, or affected by contaminants.…”
Section: Characterization Of Antibiotic Resistance By Phenotype and Wgsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent publications demonstrated that nontargeted LC-MS/MS-based approaches could analyze the susceptibility against β-lactam-based future science group www.futuremedicine.com antibiotics [32,33] in Gram-negatives. Next, by using a targeted approach (SRM mass spectrometry) was possible to detect methicillin resistance in S. aureus and virulence factors directly from positive blood cultures [34]. Furthermore, by the detection of amino acid substitutions in the GyrA protein using SRM it was possible to detect decreased quinolone susceptibility in typhoidal Salmonella isolates [35].…”
Section: Research Articlementioning
confidence: 99%